The influence of cashless lifestyle and financial literacy on the financial behavior of gen z students at the state Islamic University of North Sumatra - Gilang Saka Maulana; Juliana Nasution; Atika Atika (Indonesia Auditing Research Journal, 2026)
This research was evaluated to examine how a cashless lifestyle and financial literacy impact the financial management of Generation Z students. In this context, financial management is reflected in an individual's ability to manage expenses, develop financial plans, develop savings habits, and make wise long-term financial decisions. Sampling was conducted using a purposive sampling technique based on the Slovin formula, resulting in 100 respondents. The data collection instrument utilized a Likert-scale questionnaire, which was then processed using multiple linear regression techniques. Based on data analysis, it was found that the convenience of cashless transactions and financial literacy contributed positively and significantly to students' financial behavior. Digital payments proved to be the most dominant factor compared to financial literacy levels, as indicated by the coefficient value. The combined assessment showed a determination value of 68.7%, while the remaining 31.3% was explained by variables outside this research model. These results indicate that the acceleration of transaction technology can encourage rational and measurable financial habits when balanced with adequate financial knowledge